STRATEGI CONTENT MARKETING MEDIA SOSIAL INSTAGRAM KEDAI KOSAN DALAM MENINGKATKAN CUSTOMER ENGAGEMENT - Utami, Tami; Murtafia, Murtafia (Politeknik STIA LAN Makassar, 2025)
This study aims to analyze the content marketing strategy implemented by Kedai Kosan through the Instagram social media platform to enhance customer Engagement. The research is motivated by a decline in audience interaction with Kedai Kosan's Instagram content, despite the platform being used as a promotional tool. A qualitative descriptive approach was employed, utilizing in-depth interviews, participatory observation, and documentation for data collection. The findings reveal that Kedai Kosan's content marketing strategy includes goal setting, audience targeting, content planning and creation, content distribution, amplification, and evaluation. Content involving customers and showcasing the café's ambiance proved more effective in building Engagement. While content distribution is actively carried out via Instagram Stories, consistency in evaluation and content production remains a challenge. The study recommends increasing the frequency of video content, utilizing Instagram’s interactive features, and involving customers as part of the strategy to strengthen audience-brand connection.